(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Oligoasthenozoospermia is the condition where the two parameters, sperm count and sperm motility is altered. It depicts a decrease in the concentration and percentage of motile spermatozoa in a sperm sample and is determined by semen analysis. Researches show that nearly 50% of infertility in India is related to the male reproductive factors or diseases. Based on the study conducted by WHO from 1982 to 1985 in multicentres about 20% of infertility cases is due to male factors. Approximately 23% of Indian couples taking infertility treatment attributed the cause towards male factors. Oligoasthenozoospermia can be correlated to Sukra kshaya Lakshanas mentioned in Ashta sukra dushtis. A male patient aged 32 years with 2.5 years of married life revealed the semen volume as 2ml, Sperm concentration 1 million/ml, progressive motility 3%, Non progressive motility 2% and immotile sperms 95% with normal sperm morphology, increased viscosity and increased liquefaction time. After Ayurvedic management through Sodhana and Samana chikitsa for about 5 months revealed Normozoospermia with Sperm count 47 million/ml, progressive motility 25% and Non progressive motility15%. This shows the effectiveness of Ayurveda medicines in the case of Oligoasthenozoospermia and ensures that Ayurveda can provide spectacular outcome in the areas of Male infertility.